EFEKTIVITAS RUMPON PORTABLE PADA PERIKANAN PANCING ULUR DI BANTEN - Roza Yusfiandayani; Domu Simbolon; Weni Damayanti (Jurnal Teknologi Perikanan dan Kelautan, 2020)
Handlines are a fishing gear that is commonly used by fishermen in Banten Bay. However, the catches obtained by fishermen are few. This is because of the lack of information about the potential fishing ground that fishermen have. One of the methods to increase the effectiveness and efficiency of fishing operation is the information about the availability of fishing ground. The used of portable FADs (Fish Aggregating Devices) technology is expected to create a fishing ground so that fishing operation become more effective and efficient. The research purpose is to compare the productivity and composition of handline catching by using and without portable FAD and to determine the effectiveness of portable FAD. The method used was an experimental fishing method with 20 trips. Research showed that the dominant catches of handline fishing with portable FADs were goatfish, bream, black grouper, mackerel. Goatfish, bream, and black grouper were dominated by large sizes. The total catch of handline was 931 fish. The composition of the catch with the portable FAD was 504 of fish, while without the portable FAD was 427 of fish. The productivity of handline with portable FAD was 1.29 kg/trip, while the productivity of handline without FAD was 0.99 kg/trip. Portable FAD use during fishing operations was more effective compare to fishing operations without portable FADs.